2017
DOI: 10.4202/app.00373.2017
|View full text |Cite
|
Sign up to set email alerts
|

The Interatheriinae notoungulates from the middle Miocene Collón Curá Formation in Argentina

Abstract: The Interatheriinae (Notoungulata, Interatheriidae)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 0 publications
1
21
0
Order By: Relevance
“…The phylogenetic analysis of the Interatheriidae presented herein (like that of Fernández et al, 2021b) shows improved resolutions compared to earlier work (e.g., Cifelli, 1993;Hitz et al, 2000Hitz et al, , 2006Reguero & Prevosti, 2010;Billet, 2011;Billet & Muizon, 2013;Billet et al, 2015;García-López & Babot, 2015;Vera, 2016Vera, , 2017Vera et al, 2017Vera et al, , 2018, and represents the most complete analysis in terms of interathere genera. Interatheriidae are recovered as a clade (Fig.…”
Section: Phylogenetic Analysismentioning
confidence: 77%
See 2 more Smart Citations
“…The phylogenetic analysis of the Interatheriidae presented herein (like that of Fernández et al, 2021b) shows improved resolutions compared to earlier work (e.g., Cifelli, 1993;Hitz et al, 2000Hitz et al, , 2006Reguero & Prevosti, 2010;Billet, 2011;Billet & Muizon, 2013;Billet et al, 2015;García-López & Babot, 2015;Vera, 2016Vera, , 2017Vera et al, 2017Vera et al, , 2018, and represents the most complete analysis in terms of interathere genera. Interatheriidae are recovered as a clade (Fig.…”
Section: Phylogenetic Analysismentioning
confidence: 77%
“…However, Croft & Anaya (2020) also indicated that Interatherium is also closely related to one species of Protypotherium. Further, other authors resolve Interatherium as more closely related to Protypotherium plus Miocochilius (e.g., Reguero et al, 2003;Reguero & Prevosti, 2010;Billet, 2011;Billet & Muizon, 2013;García-López & Babot, 2015, Fernández et al, 2019b, to Plagiarthrus (e.g., Hitz et al, 2000), or even as part of a polytomy (e.g., Vera et al, 2017Vera et al, , 2018 that included a clade constituted by Mesotheriidae+Archaeohyracidae and Hegetotheriidae, triggering Vera (2017) to question the monophyly of the Interatheriidae and Interatheriinae. The latter agrees with Vera (2016) and Vera et al (2018), who must include Mesotheriidae+Hegetotheriidae and Olfieldthomasiidae, respectively, within Interatheriidae in order to consider this family monophyletic.…”
Section: Phylogenetic Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, the occurrences of notostylopids (typotheres) are restricted to Paleogene sequences in Argentina, Brazil, and Chile (McKenna and Bell 1997;Billet 2011). The absence of cementum rules out any relationship with the Interatheriinae (Vera et al 2017), while the crown lacks the distinctive flat labial face present in hegetotheriids (Cerdeño and Reguero 2015). The anteroposterior elongation of the second lobe rules out any relationship to basal hegetotheriids, while the m3 has a relatively deep labial sulcus on m3 not present in basal Interatheriinae such as †Santiagorothia and †Proargyrohyrax (Cerdeño and Reguero 2015).…”
Section: Material: a Metacarpal (Amu-curs-742) And A Distal Epiphysis Of A Metacarpal (Amu-curs-1189)mentioning
confidence: 99%
“…This is a broadly represented group in the Cenozoic of South America (Bond, 1986; Hitz et al, 2000), known mostly by the representatives of early to middle Miocene (Croft et al, 2009), being recorded from the Tinguirirican SALMA (early Oligocene) to the Huayquerian SALMA (late Miocene). The present study focuses on the comparative study of the deciduous and permanent dentition of the genera Interatherium Ameghino, 1887 (Ameghino, 1887a) from the Santacrucian SALMA and Protypotherium Ameghino, 1885, which has an unusually long stratigraphic range that extends from the Deseadan (late Oligocene) to the Huayquerian SALMA (late Miocene) (Fernández et al, 2019b) and whose monophyly has been recently questioned (e.g., Vera et al, 2017; Croft and Anaya, 2020). The obtained results allow the differentiation of several ontogenetic stages for both genera and the establishment of the pattern of eruption and replacement of the deciduous cheek teeth and the eruption sequence of molars.…”
Section: Introductionmentioning
confidence: 99%